ANALYSIS OF EXERCISES BASED ON THE STAGES OF WORKING WITH SOCIO-POLITICAL TEXTS IN FOREIGN LANGUAGE TEACHING ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article aims to analyze the effectiveness of exercises designed around socio-political texts in foreign language teaching. It delves into the pedagogical strategies employed at different stages of engagement with such texts, including comprehension, critical analysis, discussion, and reflection. The analysis highlights the potential of these texts to enhance linguistic proficiency, sociolinguistic competence, and critical thinking skills. Through a systematic review of exercises and their outcomes, the article offers insights into best practices for integrating socio-political content into language curricula, ultimately arguing for the rich educational value of socio-political texts in developing informed, critically engaged language learners.